Strategies of nurse-midwives in relation to working conditions in maternity hospitals - Manoel Luís Cardoso Vieira; Juliana Amaral Prata; Elias Barbosa de Oliveira; Fernanda Alves Bittencourt Rodrigues; Bárbara Christine Dantas Silva de Almeida; Jane Márcia Progianti (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to understand the working conditions and strategies adopted by nurse-midwives in maternity hospitals. Methods: a qualitative, descriptive, exploratory study with 20 nurse-midwives from public maternity hospitals in the city of Rio de Janeiro. Data were collected from June to September 2018 through semi-structured interviews, submitted to thematic content analysis and discussed in the light of the psychodynamics of work. Results: working conditions are inadequate due to poor infrastructure and resource deficit. Therefore, they develop defensive strategies to mitigate suffering, avoid destabilization of professional identity and minimize losses on care, through material purchase, lunch hour abdication, task reorganization and break implementation. Final Considerations: the strategies adopted hide work precariousness and suggest alienation of workers, evidencing the need to foster political awareness of this collective to promote concrete transformations in their work reality.